Tióis de importância biológica: eletroanálise em diferentes superfícies eletródicas e utilização de polímeros molecularmente impressos magnéticos para separação e avaliação de glutationa - Santos, Ana Caroline Ferreira (2018)
Biologically relevant thiols (biothiols), the most important systemic and intracellular endogenous antioxidants, play essential roles in the protection against oxidative damage, cause of several diseases. They include proteins with reduced cysteine residues and low-molecular weight (LMW) sulfur compounds. As the result of environmental, biochemical, clinical, and pharmacological importance of the thiols and disulfides, an accurate determination has gained significant attention within the analytical community. Electrochemical detection offers advantages in terms of analytical methods. The present work aims to develop electroanalytical strategies for determination of several biothiols, together with a selective approach based on molecular imprinted polymer for the separation and quantification of one of the most important biothiols, reduced glutathione (GSH). A simple and sensitive electrochemical method for the determination of N-acetyl- cysteine (NAC) and reduced glutathione (GSH), on glassy carbon electrode (GCE), using cyclic (CV) and differential pulse (DPV) voltammetries, was developed, based on the chemical reactivity between sulfides and disulfides, especially the lipoic acid (LipS 2 ). The results indicate that lipoic acid (LipS 2 ) can facilitate the electrochemical oxidation of thiolates, in a neutral pH, with a substantial increase in the anodic current, for the oxidation of NAC, GSH, cysteine (Cys) and homocysteine (HCys). LipS 2 plays an important role as a redox mediator, in solution, being regenerated, at the electrode surface, after oxidation and electron capture from the thiolates. Under optimized conditions, by DPV, the analytical parameters for NAC and GSH were obtained in the range of 1 up to 10 μmol L -1 and 1 up to 60 μmol L -1 , respectively. The quantification was performed with high sensitivity, reproducibility and submicro detection limit (LOD) of 0.27 and 0.67 μmol L -1 for NAC and GSH, respectively. The standard addition method was successfully applied to the determination of NAC and GSH, in artificial saliva and human urine samples, with excellent recovery results. The sensitivity of the method was also evaluated using a boron doped diamond electrode (BDDE) for the determination of NAC. Several analytical parameters were obtained for NAC, in the interval of 1 up to 100 μmol L -1 and nanomolar LOD of 93 nmol L -1 . The method was successfully applied to the quantification of NAC in pharmaceutical preparations (capsules, syrup and suspension), without matrix effects. The present study shows that the redox reaction between the studied thiolates and LipS 2 , in BDDE, is a promising analytical tool, which can be used for quantifying NAC in a simple, rapid, convenient, sensitive and low-cost way, for both unmodified electrodes. Magnetic Molecularly Imprinted Polymers (MMIP) are efficient analytical tools with high potential for detecting and separating analytes in complex matrices. In this work, the analyte used was GSH. Thus, the polymer synthesis for GSH identification was performed by thermopolymerization and photopolymerization, by varying the functional monomer (allylamine and acrylamide). MNIP was similarly synthesized, in the absence of GSH. MMIP was washed for removal of the imprinted molecule (GSH). The technique of analysis for the evaluation of MMIPs and MNIPs was UV/Vis spectrophotometry. The synthesized materials were physically characterized, with a significant difference between MMIPs and MNIPs, indicating that in MMIPs, a specific binding occurs, showing this device to be a promising material for GSH detection and separation.